The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Spatial footprint of maritime vessels in the waters of a fast-growing coastal megalopolis - Stephen D.J. Lang; Philip D. Doherty; Brendan J. Godley; Shing Yip Lee; Felix Leung; Manmohan D. Sharma; Kristian Metcalfe (Marine Policy, 2025)

Heliophysics and space weather information architecture and innovative solutions: Current status and ways forward - Arnaud Masson; Shing F. Fung; Enrico Camporeale; Masha M. Kuznetsova; Stefaan Poedts; Julie Barnum; Rebecca Ringuette; D. De Zeeuw; Shawn Polson; Viacheslav M. Sadykov; Vicente Navarro; Brian Thomas; et al. (Advances in Space Research, 2024)

Assessments of carbon nanotubes toxicities in zebrafish larvae using multiple physiological and molecular endpoints - Gilbert Audira; Jiann-Shing Lee; Ross D. Vasquez; Marri Jmelou M. Roldan; Yu-Heng Lai; Chung-Der Hsiao (Chemico-Biological Interactions, 2024)

Rise and fall of an avian oasis: Tracking the impacts of land use change in a key coastal wetland in the world's largest megalopolis - Felix Leung; Philip D. Doherty; Mingfeng Liu; Kristian Metcalfe; Brendan Godley; Shing Yip Lee (Science of The Total Environment, 2024)

SPASE metadata as a building block of a heliophysics science-enabling framework - Shing F. Fung; Arnaud Masson; Lee F. Bargatze; Todd King; Rebecca Ringuette; Robert M. Candey; Chiu Wiegand; Lan K. Jian; Darren De Zeeuw; Karin Muglach; Ryan M. McGranaghan; D. Aaron Roberts; et al. (Advances in Space Research, 2023)

Effect of biomass retention time on performance and fouling of a stirred membrane photobioreactor - Bao-Trong Dang; Xuan-Thanh Bui; Thanh-Tin Nguyen; Huu Hao Ngo; Long D. Nghiem; Ky-Phuong-Ha Huynh; Thi-Kim-Quyen Vo; Thi-Dieu-Hien Vo; Chitsan Lin; Shiao-Shing Chen (Science of The Total Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Understanding the mechanisms of trace organic contaminant removal by high retention membrane bioreactors: a critical review - Muhammad B. Asif; Ashley J. Ansari; Shiao-Shing Chen; Long D. Nghiem; William E. Price; Faisal I. Hai (Environmental Science and Pollution Research, 2019)

Optimising Seagrass Conservation for Ecological Functions - Christopher J. Henderson; Tim Stevens; Shing Y. Lee; Ben L. Gilby; Thomas A. Schlacher; Rod M. Connolly; Jan Warnken; Paul S. Maxwell; Andrew D. Olds (Ecosystems, 2019)

Mechanistic relationships between hepatic genotoxicity and carcinogenicity in male B6C3F1 mice treated with polycyclic aromatic hydrocarbon mixtures - Tracie D. Phillips; Molly Richardson; Yi-Shing Lisa Cheng; Lingyu He; Thomas J. McDonald; Leslie H. Cizmas; Stephen H. Safe; Kirby C. Donnelly; Fen Wang; Bhagavatula Moorthy; Guo-Dong Zhou (Archives of Toxicology, 2015)

Effects of probiotics supplementation on gastrointestinal permeability, inflammation and exercise performance in the heat - Cecilia M. Shing; Jonathan M. Peake; Chin Leong Lim; David Briskey; Neil P. Walsh; Matthew B. Fortes; Kiran D. K. Ahuja; Luis Vitetta (European Journal of Applied Physiology, 2014)

Effect of whole-body mild-cold exposure on arterial stiffness and central haemodynamics: a randomised, cross-over trial in healthy men and women - Sibella G. King; Kiran D. K. Ahuja; Jezreel Wass; Cecilia M. Shing; Murray J. Adams; Justin E. Davies; James E. Sharman; Andrew D. Williams (European Journal of Applied Physiology, 2013)

Introduction to the TAIGER special issue of Marine Geophysical Research - Kirk D. McIntosh; Char-Shine Liu; Chao-Shing Lee (Marine Geophysical Research, 2012)

A review of the pharmacobiotic regulation of gastrointestinal inflammation by probiotics, commensal bacteria and prebiotics - L. Vitetta; D. Briskey; E. Hayes; C. Shing; J. Peake (Inflammopharmacology, 2012)

Features discriminating SARS from other severe viral respiratory tract infections - T. H. Rainer; N. Lee; M. Ip; A. P. Galvani; G. E. Antonio; K. T. Wong; D. P. N. Chan; A. W. H. Ng; K. K. Shing; S. S. L. Chau; P. Mak; P. K. S. Chan; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Seasonal and Interannual Variability in the Distribution of Surface Nutrients and Dissolved Inorganic Carbon in the Northern North Pacific: Influence of El Niño - Chi Shing Wong; Nathalie A. D. Waser; Yukihiro Nojiri; Wm. Keith Johnson; Frank A. Whitney; John S. C. Page; Jiye Zeng (Journal of Oceanography, 2002)